Concentration-dependent interactive toxicity of cadmium and mercury: Non-negligible effects on phytoremediation by indigenous Artemisia lavandulaefolia - Gangyang Zhang; Guo Chen; Rui Yang; Chunlian Bai; Weiyuhao Yang; Juan Zhang; Xuyang Yin; Fang Yang; Chandra Shekhar Seth; Haitao Liu (Ecotoxicology and Environmental Safety)
The indigenous species Artemisia lavandulaefolia, widespread in areas co-contaminated with Cd and Hg, has the potential for phytoremediation. However, the mechanisms that underlie these plants' resistance to combined Hg and Cd stress are unelucidated. The influence of the dosage of one metal on another has also not been adequately quantified. We investigated the combined and interactive effects of varying doses of Cd and Hg on this species' growth, heavy metal accumulation, and physiological responses. We found that increased Hg and Cd in the co-contaminants inhibited biomass by 16–59 %. The interaction between these heavy metals on growth was concentration-dependent, with an antagonistic effect (concentration addition index (CAI) and effect addition index (EAI) < 0) at low concentrations and an additive effect at high concentrations. An increase in one metal had a beneficial effect on the aboveground accumulation of the other metal, reaching bioconcentrations of 20.16 and 2.25 for Cd and Hg, respectively. Furthermore, the elevation of Cd in the solution increased the proportion of Hg in the cell walls to 31.5 %; however, increasing the Hg dose did not change the Cd concentration in this substructure. Our results also demonstrate that different physiological responses occurred with increased Hg and Cd in the co-contaminants. The elevation of Hg in the mixture had a greater effect on photosynthetic systems than the increased Cd levels. The antioxidant systems of roots and leaves play important roles in attenuating Hg and Cd stress, respectively. Principal component analysis (PCA) revealed concentration-dependent trade-offs between heavy metal accumulation and plant growth and between the above- and belowground antioxidant activities of Artemisia lavandulaefolia for the first time. With increasing Hg, plants preferred to stimulate belowground antioxidant activity, whereas high concentrations of Cd followed the opposite trend. This study provides a theoretical basis for the phytoremediation of this species under combined heavy metal pollution. It highlights that the concentration-dependent interaction between Hg and Cd on plant toxicity should not be ignored during phytoextraction in co-contaminated environments.